2010
DOI: 10.1016/j.childyouth.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Assets and child well-being in developed countries

Abstract: Although there is no universal approach to offering Child Development Accounts (CDAs), this paper introduces a framework for an age-based conceptual model that describes how such accounts might influence indicators of child wellbeing. With a focus on optimal age-appropriate development beginning at birth and ranging through young adulthood, the model incorporates research from multiple disciplines to include direct effects, indirect effects and critical milestones. We review empirical evidence from national da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Financial socialization theory contends that families provide an important context in which young people acquire financial knowledge and behaviors, including saving (Ashby et al 2011;Bowman 2011;Danes 1994;GrinsteinWeiss et al 2011;Lunt and Furnham 1996;Serido et al 2010;Shim et al 2009Shim et al , 2010Sonuga-Barke and Webley 1993;Ward et al 1977;Williams et al 2010). Financial socialization is provided through families' intentional instruction and young people's observations of their families as models (Moschis 1985;Williams et al 2010).…”
Section: The Role Of Families' Savings and Accumulated Assets For Youmentioning
confidence: 96%
See 3 more Smart Citations
“…Financial socialization theory contends that families provide an important context in which young people acquire financial knowledge and behaviors, including saving (Ashby et al 2011;Bowman 2011;Danes 1994;GrinsteinWeiss et al 2011;Lunt and Furnham 1996;Serido et al 2010;Shim et al 2009Shim et al , 2010Sonuga-Barke and Webley 1993;Ward et al 1977;Williams et al 2010). Financial socialization is provided through families' intentional instruction and young people's observations of their families as models (Moschis 1985;Williams et al 2010).…”
Section: The Role Of Families' Savings and Accumulated Assets For Youmentioning
confidence: 96%
“…If families have savings, for example, young people may be more likely to have savings of their own or to observe their families making deposits into savings accounts. However, existing disparities in families' savings and accumulated assets suggest that financial socialization may be transmitted unequally to young people (Danes 1994;Grinstein-Weiss et al 2011;Williams et al 2010). This is supported by research examining the role of families' intergenerational transfers for transmitting racial disparities in accumulated assets (Charles and Hurst 2003;Cheng 1996;De Nardi 2004;Gale and Scholz 1994;Keister 2003;Mishel et al 2009;Oliver and Shapiro 2006;Shapiro 2004).…”
Section: The Role Of Families' Savings and Accumulated Assets For Youmentioning
confidence: 98%
See 2 more Smart Citations
“…A seminal work by Sherraden () posits that assets play a unique, crucial role in promoting life chances and long‐term wellbeing of children and families. A growing body of evidence indicates that building assets, even at a modest level, has positive effects on youth development and wellbeing in both developed and developing countries (Chowa, Ansong & Masa, ; Elliott & Beverly, , ; Ssewamala & Ilic, ; Williams Shanks, Kim, Loke & Destin, ). For example, Williams Shanks and her colleagues (Williams Shanks et al ., ) have reviewed extensive research on the role of assets in child wellbeing in developed countries and concluded that assets positively influence various domains of child wellbeing such as educational, economic, psychological and behavioural outcomes in both direct and indirect ways.…”
mentioning
confidence: 99%